Implementasi Program Roots Anti Perundungan di SMK Negeri 3 Pematangsiantar - Istiqomatuddiniyyah Panggabean; Arief Wahyudi (LPPM Institut Pendidikan Nusantara Global, 2025)
The Roots Anti-Bullying Program is a peer-based bullying prevention initiative developed by Puspeka-Kemendikbudristek in collaboration with UNICEF, focusing on the formation of student change agents as drivers of healthy interaction within schools. This study aims to describe the implementation and impact of the Roots Anti-Bullying Program at SMK Negeri 3 Pematangsiantar. It employs a qualitative case study method, grounded in George C. Edwards III's policy implementation theory. The research was conducted at SMK Negeri 3 Pematangsiantar, with informants including guidance and counseling teachers, teacher representatives, teacher facilitators, parents, change agents, and student representatives from various grades and majors. Data collection involved both primary and secondary sources. Data analysis followed the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results show that (1) the program was implemented systematically, with stages including facilitator training, school environment surveys, recruitment of change agents, training of change agents, and the culminating event known as Roots Day; and (2) the program's impact included a decrease in verbal bullying behavior, increased social awareness, and enhanced empathy among students.